2013
DOI: 10.1093/jrr/rrt081
|View full text |Cite
|
Sign up to set email alerts
|

Optimized enzymatic dual functions of PaPrx protein by proton irradiation

Abstract: We investigated the effects of proton irradiation on the function and structure of the Pseudomonas aeruginosa peroxiredoxin (PaPrx). Polyacrylamide gel demonstrated that PaPrx proteins exposed to proton irradiation at several doses exhibited simultaneous formation of high molecular weight (HMW) complexes and fragmentation. Size-exclusion chromatography (SEC) analysis revealed that the number of fragments and very low molecular weight (LMW) structures increased as the proton irradiation dose increased. The pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…However, earlier attempts to manipulate 2-Cys Prx to enhance one of these activities have compromised the efficiency of the other activity (An et al, 2011a;Hong et al, 2012). Recently, however, Park et al (2014) have reported that proton irradiation can enhance both the peroxidase and the chaperone activity of PaPrx (2-Cys Prx). It has also been observed that the dual function of 2-Cys Prx can be regulated by an additional Cys on the a-helix region between two active Cys residues (An et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…However, earlier attempts to manipulate 2-Cys Prx to enhance one of these activities have compromised the efficiency of the other activity (An et al, 2011a;Hong et al, 2012). Recently, however, Park et al (2014) have reported that proton irradiation can enhance both the peroxidase and the chaperone activity of PaPrx (2-Cys Prx). It has also been observed that the dual function of 2-Cys Prx can be regulated by an additional Cys on the a-helix region between two active Cys residues (An et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%